Perilaku Pencegahan HIV?AIDS pada Petugas Balawista - I Ketut Gama; Ni Kadek Dwi Jayanti; I Wayan Suardana (Jurnal Gema Keperawatan, 2016)
This purpose study to describe the behavior the prevention of HIV / AIDS on Balawista officers at Kuta Beach. This research uses cross sectional. Technique sampling in this study is Non Probability Sampling. This research was conducted in April 2016. The results is knowledge of good 26 people (81.3%), good attitude 23 people (71.9%), and good action 18 people (56.3%). Main of this study indicate that the most of Balawista officers have good behavior in the prevention of HIV / AIDS. Although there Balawista officers who have less action as much as 2 people (6.2%).